Classification of Scientific Papers based on their Nature and Format - Arslonbek Saidov; Olimboy Shavkatov; TEMUR A’ZAMOV (Journal of Artificial Intelligence and Digital Economy, 2024)
The effective categorization and classification of scientific papers based on their nature and format are vital due to the extensive volume of published scientific literature. This research endeavors to delve into the intricate realm of classifying scientific papers, concentrating on discerning categories such as dissertations, scientific articles, theses, and other pertinent types. By meticulously examining the unique attributes, objectives, and structural elements inherent in each paper type, this study aims to furnish researchers, students, and readers with a comprehensive comprehension of the diverse assortment of scientific papers and their idiosyncratic features. Moreover, this article deliberates upon the significance of accurate classification with regard to proficient literature retrieval, knowledge dissemination, and academic publication. Additionally, it scrutinizes the conceivable challenges and deliberations involved in formulating classification systems for scientific papers, encompassing the dynamic nature of scientific communication and the emergence of alternative formats such as preprints and data papers. By augmenting our grasp of scientific paper classification, this research contributes to the enhancement of accessibility, organization, and utilization of scientific knowledge.